Development of a procedure for the sequential extraction of substances binding trace elements in plant biomass - Pavlíková, Daniela; Pavlík, Milan; Vasícková, Sona; Száková, Jirina; Vokác, Karel; Balík, Jirí; Tlustos, Pavel (Analytical and bioanalytical chemistry, 2005)
This work investigates how the amounts of some important substances in a plant, and their behaviour inside the plant, depend on the levels of stress placed on the plant. To this end, model plant spinach (Spinacia oleracea L.) was cultivated on soil treated with sewage sludge. The sewage sludge contained various trace elements (As, Cd, Cu, Zn), and the uptake of these trace elements placed the plant under stress. Following this, a sequential extraction procedure was employed to determine the levels and distributions of trace elements within the most important groups of compounds present in the spinach plants. Since the usual five-step sequential extraction procedure provides only general information on the distributions of elements within individual groups of organic compounds, due to the wide range of organic compounds within the individual fractions, this scheme was extended and improved through the addition of two solvent extraction steps-a butanol step (between the ethyl acetate and methanol solvent steps) and an H(2)O step (after the methanol+H(2)O solvent step). The distributions and levels of the trace elements within the main groups of compounds in spinach biomass was investigated using this new seven step sequential extraction (water free solvents: petroleum ether (A) --> ethyl acetate (B) --> butanol (C) --> methanol (D) --> water solvents: methanol+H(2)O (1+1; v/v) (E) --> H(2)O (F) --> methanol+H(2)O+HCl (49.3+49.3+1.4; v/v/v) (G)). The isolated fractions were characterized using IR spectroscopy and the trace element contents were determined in the individual fractions. Lipophilic compounds with low contents of Cd, Cu and Zn were separated in the first two fractions (A, B). Compounds with higher As contents (11.5-12.8% of total content) were also extracted in the second fraction, B. These two fractions formed the smallest portion of the isolated fractions. Low molecular compounds from secondary metabolism and polar lipids were separated in the third (C) and fourth (D) fractions, and high molecular compounds (mainly polypeptides and proteins) separated in the fifth and sixth fractions (E, F). The addition of the H(2)O solvent step was particularly useful for separating compounds that have a significant impact on trace element bounds. The methanol fraction was dominant for all treatments, and a significant decrease in the spinach biomass separated in this fraction was observed when the soil was treated with sewage sludge. Most of the As (35.5-38.8% of total content), Cu (45.0-51.6%) and Zn (39.8-47.2%) was also determined in this fraction. The G fraction (obtained after acid hydrolysis) contained polar compounds. Most of the Cd was also found in this fraction, as was a significant amount of Zn. Non-extractable residues formed the last fraction (polysaccharides, proteins).
Keywords: Spectrophotometry, Infrared; Trace Elements; biomasa; stopové prvky; Biomass; spektrofotometrie infračervená; Spinacia oleracea